HYPOCALCEMIA IN TOTAL VERSUS SUBTOTAL THYROIDECTOMY - Sajid, Tahira; Naqvi, Syeda Rifaat Qamar; Sajid, Zara; Sajid, Fatima; Akbar, Ismail; Mallhi, Muhammad Ayub Ashraf (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the occurrence of hypocalcemia in patients undergoing subtotal and total thyroidectomy.Study Design: Comparative prospective study.Place and Duration of Study: Surgical departments of Ayub Teaching Hospital, Abbottabad and Combined Military Hospital, Rawalpindi, from Mar 2018 to Feb 2020.Methodology: A total of 171 patients were selected for this study and they were divided into 2 groups. Group 1 consisted of 95 patients undergoing Total thyroidectomy whereas group 2 had 76 patients undergoing Subtotal thyroidectomy. It was a comparative prospective study and the groups were made by convenience sampling. The data was analyzed by SPSS-23.Results: In total thyroidectomy group Hypocalcemia was detected after 48 hours in 34 patients (35%) while in subtotal thyroidectomy group hypocalcemia was detected in 20 patients (28%). Tests for hypocalcemia were also done after two months of surgery and low levels were detected in 7 patients (7.5%) who had total thyroidectomy and in 2 patients (5%) in the group undergoing subtotal thyroidectomy. There was no significant difference in hypocalcemia after 48 hour (p=0.22) and 2 months postoperatively (p=0.6) between patients of Total Thyroidectomy and Subtotal Thyroidectomy.Conclusion: Total thyroidectomy is not associated with increased risk of permanent hypocalcemia as compared to Subtotal thyroidectomy. Because of its advantages Total thyroidectomy should be the preferred surgical procedure for patients presenting with benign euthyroid multi nodular goiter.